Preparation method of sulfide-based solid electrolyte

By using wet crushing process and ketone solvents as dispersion stabilizers during the microparticleization process of sulfide-based solid electrolyte, the problem of particle size control and recovery reduction in the process of microparticleization is solved, and efficient particle size control and recovery improvement is achieved, while avoiding the reduction of ionic conductivity.

CN119816973APending Publication Date: 2025-04-11LOTTE ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380066146.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-08-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing sulfide-based solid electrolytes are difficult to control the particle size during the microparticleization process, and they are prone to adhere to the pulverizing medium or re-aggregate during wet pulverization, resulting in a decrease in recovery and an ionic conductivity will also be affected.

Method used

The sulfide-based solid electrolyte is prepared by a wet pulverization process, and an organic solvent is used as a dispersion medium and a ketone solvent is used as a dispersion stabilizer to control particle size and inhibit the aggregation and adhesion of the solid electrolyte.

Benefits of technology

The preparation of a sulfide-based solid electrolyte with a desired particle size is achieved, which improves the recovery of the solid electrolyte and suppresses the reduction of the ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816973A_ABST
    Figure CN119816973A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing sulfide-based solid electrolyte with required particle size through wet crushing. The invention provides a preparation method of a sulfide-based solid electrolyte. The preparation method comprises the following steps: preparing a sulfide-based solid electrolyte material; and a micronization step in which the sulfide-based solid electrolyte material is subjected to wet grinding using an organic solvent as a dispersion medium used in the wet grinding and using a ketone-based solvent as a dispersion stabilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a sulfide-based solid electrolyte, and more particularly, to a method for preparing a sulfide-based solid electrolyte in which an assembled material is micronized by wet pulverization to control the particle size. Background Art

[0002] All-Solid-State Battery refers to a battery in which the electrolyte in the battery assembly is replaced by a solid electrolyte instead of the existing liquid electrolyte. In this case, the electrolyte and separator required for the existing lithium-ion battery are removed and replaced by a solid electrolyte. Therefore, compared with the existing battery using a liquid electrolyte, the all-solid-state battery has no risk of battery explosion or fire, and the manufacturing process is simplified. It also has the potential to achieve high energy density, so it has attracted much attention as the next generation of secondary batteries.

[0003] Among inorganic substances, sulfide-based solid electrolytes have attracted much attention as solid electrolytes (Solid State Electrolyte, SSE) for all-solid-state batteries. However, for most sulfide-based solid electrolytes, after mixing raw materials such as Li2S, P2S5, LiCl and undergoing long-term high-energy grinding, in order to increase ionic conductivity by increasing crystallinity, after a calcination process, the particle size of the solid electrolyte will increase in this calcination process. Therefore, according to the battery core application site of the solid electrolyte, it is necessary to appropriately micronize the synthesized assembly material. However, sulfide-based solid electrolytes are soft materials, so there is a disadvantage that it is difficult to micronize. In addition, when the solid electrolyte is micronized by mechanical pulverization, the solid electrolyte adheres to the pulverization medium or re-aggregates, so that the recovery rate of the solid electrolyte is also reduced. In particular, when wet pulverization is used in the micronization process, impurities such as solvents used as dispersion media remain, so there is also a problem of reduced ionic conductivity of the solid electrolyte. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In order to solve the problems of the prior art as described above, an object of the present invention is to provide a method for preparing a sulfide-based solid electrolyte having a desired particle size by wet pulverization.

[0006] In addition, the object of the present invention is to provide a method for preparing a sulfide-based solid electrolyte, which can suppress the phenomenon that the solid electrolyte is firmly attached to the pulverizing medium or re-aggregated during wet pulverization, and can easily deagglomerate, thereby improving the recovery rate of the solid electrolyte.

[0007] Furthermore, an object of the present invention is to provide a method for preparing a sulfide-based solid electrolyte using a wet pulverization process that suppresses a decrease in ion conductivity.

[0008] (II) Technical solution

[0009] In order to achieve the above technical problem, the present invention provides a method for preparing a sulfide-based solid electrolyte, which comprises the following steps: preparing a sulfide-based solid electrolyte material as a compound containing Li, A (A is at least one of P, Si, Ge, Al, B and Sn) and S; and a micronization step of wet-crushing the sulfide-based solid electrolyte material, wherein an organic solvent is used as a dispersion medium used in the wet crushing, and a ketone solvent is used as a dispersion stabilizer.

[0010] In the present invention, the content of the dispersion stabilizer may be 0.01-10 parts by volume relative to 100 parts by volume of the dispersion medium.

[0011] Furthermore, in the present invention, the content of the dispersion stabilizer may be 0.1-2 parts by volume relative to 100 parts by volume of the dispersion medium.

[0012] In the present invention, two hydrocarbon groups or hydrocarbon derivatives in the ketone solvent are connected to a carbonyl group (C=O), and the number of carbon atoms of at least one of the two hydrocarbon groups or hydrocarbon derivatives is preferably less than 5. In particular, the ketone solvent may include at least one of methyl isobutyl ketone, acetone, butyl methyl ketone, diethyl ketone, diisobutyl ketone, methyl ethyl ketone, methyl pentyl ketone and methyl propyl ketone.

[0013] In the present invention, the organic solvent may include at least one of a hydrocarbon-based non-polar solvent and an aromatic compound.

[0014] In the present invention, after the pulverizing step, a step of removing the dispersion medium and the dispersion stabilizer to recover the powder may be further included, wherein the weight of the recovered powder may be more than 80% of the weight of the added powder.

[0015] (III) Beneficial effects

[0016] According to the present invention, a sulfide-based solid electrolyte having a desired particle size by wet pulverization can be provided. In addition, according to the present invention, the phenomenon that the solid electrolyte is firmly attached to the pulverization medium or re-aggregated during wet pulverization can be suppressed, and the agglomeration can be easily deagglomerated, so the recovery rate of the solid electrolyte can be improved. In addition, according to the present invention, a sulfide-based solid electrolyte can be prepared by applying a wet pulverization process that suppresses the reduction of ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a graph showing the particle size analysis results of Examples 1 to 4 and Comparative Examples 1 to 4, sorted according to the amount of balls used in the pulverization process.

[0018] Figure 2 This is a graph showing the recovery rate results of Examples 1 to 4 and Comparative Examples 1 to 4, sorted according to the amount of balls used in the pulverization process.

[0019] Figure 3 This is a graph summarizing the particle size analysis results of the powder samples of Examples 5 to 11 and Comparative Example 5.

[0020] Figure 4 is a graph plotting the recovery rate measurement results of Examples 5 to 11 and Comparative Example 5.

[0021] Figure 5 : is a graph comparing the measurement results of ion conductivity and particle size of Examples 5 to 11 and Comparative Example 5.

[0022] Figure 6 It is a graph showing the calculation results of the ratio of ion conductivity / volume in Examples of the present invention.

[0023] Figure 7 is a graph showing the XRD analysis results of a powder sample prepared in one example of the present invention.

[0024] Figure 8 This is a diagram summarizing the particle size analysis results of powder samples obtained in additional examples of the present invention.

[0025] Fig. 9 It is a graph which summarizes the measurement results of the recovery rates of powder samples obtained in the additional examples of the present invention.

[0026] Fig.10 This is a graph comparing the measurement results of ion conductivity and particle size of Example 7 and Examples 12 to 18 with Comparative Example 5.

[0027] Fig.11 This is a graph showing the calculated ion conductivity / volume ratio of powder samples obtained in additional examples of the present invention.

[0028] Fig.12 It is a graph showing the analysis results of the electrical conductivity of Examples of the present invention and Comparative Examples. Best Mode for Carrying Out the Invention

[0029] The embodiments described in this specification and the structures shown in the accompanying drawings are only the most preferred embodiments of the present invention and do not represent the entire technical concept of the present invention. Therefore, it should be understood that the present invention may include various equivalents and modifications that can replace them. Below, with reference to the accompanying drawings, the embodiments of the present invention are described in detail.

[0030] In the method for preparing a solid electrolyte of the present invention, the sulfide-based solid electrolyte material may be a compound containing Li, A and S, and A may contain at least one of P, Si, Ge, Al, B and Sn. S in the sulfide-based solid electrolyte compound may be partially substituted by halogen elements (F, Cl, Br, I), oxygen (O), nitrogen (N), etc.

[0031] The preparation method of the solid electrolyte according to the present invention can be applied to sulfide-based solid electrolytes having, for example, Li2S-P2S5 glass, Li-PS glass ceramics, argyrodite, thiolithium superion conductor (Thio-LISICON), and LGPS crystal structures.

[0032] The method for preparing the solid electrolyte according to the present invention can be particularly applied to 7-x PS 6-x X x (wherein X is at least one element selected from F, Cl, Br, I, O and N, 0≤x≤2) of the structural formula of argyrodite-type solid electrolyte.

[0033] Hereinafter, each step of the preparation method of the present invention will be described in detail.

[0034] A. Synthesis of solid electrolytes

[0035] A sulfide-based solid electrolyte having a desired composition can be synthesized using a known method, for example, a solid phase synthesis method in which a lithium source, a sulfur source, a phosphorus source, and a halogen source are pulverized and mixed, or a liquid phase synthesis method in which each source is dissolved in a solvent and then synthesized.

[0036] After synthesizing a solid electrolyte with a desired composition, a calcination process may be performed to improve ionic conductivity by increasing crystallinity. For example, for the synthesis of Li6PS5Cl compounds, it may be performed at a temperature of 400-600°C for 1-12 hours in an inert atmosphere such as Ar or N2.

[0037] The above synthesis method is an exemplary method, and other powders synthesized by any method can be used in the solid electrolyte synthesis process of the present invention.

[0038] B. Control of solid electrolyte particle size

[0039] In order to control the particle size of the solid electrolyte, a wet pulverization process is used. The wet pulverization process can be performed using a dispersion medium and a ball mill, a bead mill, a planetary ball mill, or the like.

[0040] In the wet pulverization process of the present invention, an organic solvent can be used as a dispersion medium, and preferably a hydrocarbon non-polar solvent or an aromatic compound can be used. For example, the hydrocarbon non-polar solvent can use various solvents such as hexane, heptane, octane, nonane, decane, undecane, dodecane, and mixtures thereof, and the aromatic compound can use various solvents such as benzene, ethylbenzene, durene, diethylbenzene, styrene, xylene, and toluene.

[0041] In the wet pulverization process of the present invention, a dispersion stabilizer is used to improve the pulverization efficiency. A ketone solvent is preferably used as the dispersion stabilizer. In the present invention, two hydrocarbon groups or hydrocarbon derivatives in the ketone compound as a dispersion stabilizer are connected to a carbonyl group (C=O). In order to facilitate the removal of the dispersion stabilizer, the number of carbon atoms of at least one of the two hydrocarbon groups or hydrocarbon derivatives is preferably 10 or less, and particularly preferably 5 or less. For example, one selected from methyl isobutyl ketone, acetone, butyl methyl ketone, diethyl ketone, diisobutyl ketone, methyl ethyl ketone, methyl amyl ketone, methyl propyl ketone, dipropyl ketone, ethyl amyl ketone, ethyl butyl ketone, ethylpropyl ketone, ethyl isopropyl ketone or a mixture thereof can be used.

[0042] In the present invention, the ketone used as a dispersion stabilizer inhibits the aggregation of the solid electrolyte during the pulverization process, thereby preparing a powder with a fine particle size. In addition, the ketone used as a dispersion stabilizer inhibits the solid electrolyte powder from firmly adhering to the pulverization medium such as balls, thereby improving the pulverization yield. In addition, in the micronization process of the present invention, the dispersion stabilizer can inhibit the reduction of ionic conductivity caused by the micronization process by improving the pulverization efficiency.

[0043] In the present invention, the content of the dispersion stabilizer is 0.01-10 parts by volume, preferably 0.1-2 parts by volume, relative to 100 parts by volume of the dispersion medium. Within the above concentration range, the micronized powder shows a more improved average particle size. However, when the content of the dispersion stabilizer exceeds 10 parts by volume, a particle size distribution similar to that without the dispersion stabilizer is shown. Therefore, from the perspective of particle size distribution, the content of the dispersion stabilizer is preferably less than 10 parts by volume. In addition, in terms of ionic conductivity, the content of the dispersion stabilizer is preferably 0.01-10 parts by volume, particularly preferably 0.1-2 parts by volume.

[0044] Generally, when the solid electrolyte is micronized, the ionic conductivity decreases. The reason why the ionic conductivity decreases is that: i) as the particle size decreases, the interface between the particles increases, thereby increasing the total resistance, and ii) the crystallinity of the solid electrolyte decreases when it passes through the pulverization process. Therefore, it is difficult to directly compare the ionic conductivity of solid electrolytes having different particle sizes. In the present invention, in order to compare the ionic conductivity of solid electrolytes having different particle sizes, the ratio (R) of the ionic conductivity to the particle volume is defined as follows.

[0045] R = (ionic conductivity) / (volume of particle)

[0046] For the volume of particles, the particle size is calculated using the following formula, assuming that the particle being measured is spherical.

[0047] (volume of particle) = 4 / 3πr 3 , r = (particle size, D50) / 2

[0048] From this, assuming the particles are of the same size, the ratio of ionic conductivity / particle volume is calculated and compared.

[0049] In the present invention, the specific micronization process using the above-mentioned dispersion medium and dispersion stabilizer can be appropriately designed. As an example, the micronization process can include a coarse pulverization process and a fine pulverization process. In the case of a ball mill or a planetary mill, a large-diameter ball is used in the coarse pulverization process, and a small-diameter ball is used in the fine pulverization process, so that the pulverization efficiency can be improved.

[0050] After the pulverization process, the dispersion medium and dispersion stabilizer can be removed by various methods such as filtration, sedimentation or vacuum drying.

[0051] The particle size of the sulfide-based solid electrolyte powder obtained through the above process in the present invention may have the following characteristics.

[0052] 2.5 <D 50 (μm)<3.5,

[0053] 0.9 < Span < 1.35 (where the span of the particle size distribution (Span) = (D 90 - D 10 ) / D 50 )

[0054] In addition, the recovery rate, which represents the ratio of the weight of the recovered powder to the weight of the added powder in the present invention, can be 80% or more, 85% or more, or 90% or more.

[0055] Furthermore, the ionic conductivity of the sulfide-based solid electrolyte powder of the present invention is preferably 1.0 mS / cm or more, 1.1 mS / cm or more, or 1.2 mS / cm or more. In the present invention, sulfide-based solid electrolyte powder with an ionic conductivity of up to 1.4 mS / cm can be prepared.

[0056] In the present invention, the ratio (R) of the ionic conductivity to the particle volume can be 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.1 or more. However, it should be noted that the ratio of the ionic conductivity to the particle volume in the present invention is a relative value that can vary depending on the type of solid electrolyte, particle size, etc. Detailed Embodiments

[0057] Hereinafter, the present invention will be described in detail by way of examples.

[0058] <Synthesis Example of Li6PS5Cl>

[0059] Weigh Li2S, P2S5, and LiCl as starting materials and perform pulverization and mixing in a planetary ball mill. Specifically, use Φ15 mm balls in the PM400 planetary mill of Retsch and perform dry milling at a rotational speed of 200 - 350 rpm for 2 - 12 hours (PM400).

[0060] Next, the milled starting materials are calcined by heat treatment at a temperature of 550 °C in an inert atmosphere for 6 hours to synthesize Li6PS5Cl.

[0061] <Example 1>

[0062] Weigh 100 g of Li6PS5Cl synthesized in the experimental example, 400 g of Φ10 mm balls, 250 ml of decane, and 0.25 ml of methyl isobutyl ketone and place them in a 500 ml wide-mouth jar (Jar), and first perform coarse pulverization using a planetary ball mill.

[0063] Next, the coarsely crushed Li6PS5Cl powder was recovered and finely crushed to adjust the particle size. 100 g of Φ3 mm balls, 10 g of coarsely crushed Li6PS5Cl, 250 ml of decane and 12.5 ml of methyl isobutyl ketone were weighed and placed in a 500 ml wide-mouth bottle and crushed using a planetary ball mill.

[0064] After the pulverization is completed, the balls are separated and filtered with a filter, and then the solids are collected and vacuum dried at a temperature of 80-120°C for 3-12 hours to prepare a powder sample. The weight of Li6PS5Cl before pulverization is taken as the added amount, the content of the powder remaining after vacuum drying is taken as the recovered amount, and the recovery rate is measured according to the following formula.

[0065] <Mathematical formula 1>

[0066] (Recovery rate) = (recovery amount) / (added amount) 100

[0067] <Example 2 to Example 4>

[0068] Solid electrolyte powders were prepared under the same conditions as in Example 1, except that the amounts of balls used as a dispersion medium in the fine pulverization step used in Examples 2 to 4 were 200 g, 300 g, and 400 g, respectively.

[0069] <Comparative Examples 1 to 4>

[0070] Solid electrolyte powders were prepared under the same conditions as in Examples 1 to 4, respectively, except that no dispersion stabilizer was added in the fine pulverization step of Comparative Examples 1 to 4. That is, in Comparative Examples 1 to 4, the amounts of balls used as a dispersion medium in the fine pulverization step were 100 g, 200 g, 300 g, and 400 g, respectively, 250 ml of decane was used as the dispersion medium, and no dispersion stabilizer was added.

[0071] <Example 5>

[0072] 100 g of Φ3 mm balls, 10 g of roughly pulverized Li6PS5Cl, 150 ml of decane, and 0.15 ml of methyl isobutyl ketone were weighed and placed in a 500 ml wide-mouth bottle, and pulverized using a planetary ball mill.

[0073] After the pulverization was completed, the balls were separated and filtered with a filter, and then the solids were collected and vacuum dried at a temperature of 80-120° C. for 3-12 hours, thereby preparing a powder sample.

[0074] <Example 6 to Example 11>

[0075] A solid electrolyte powder sample was prepared by the same method as in Example 5, except that the content of the dispersion stabilizer was changed.

[0076] That is, the concentration of the dispersion stabilizer was changed to 0.5 parts by volume, 1.0 parts by volume, 2.0 parts by volume, 5.0 parts by volume, 7.5 parts by volume and 10 parts by volume based on 100 parts by volume of the dispersion medium, and the Li6PS5Cl powder was crushed to prepare powder samples of Examples 6 to 11, respectively.

[0077] <Comparative Example 5>

[0078] A powder sample of Comparative Example 5 was prepared by the same method as Example 5, except that no dispersion stabilizer was used.

[0079] The concentrations of the dispersion stabilizers of Examples 5 to 11 and Comparative Example 5 (indicated as parts by volume of the dispersion stabilizer relative to 100 parts by volume of the dispersion medium) are shown in the following table.

[0080] [Table 1]

[0081]

[0082] <Example 12 to Example 18>

[0083] The concentration of the dispersion stabilizer was fixed at 1 part by volume, and the type of the dispersion stabilizer was changed to prepare powder samples under the same process conditions as Example 7. The dispersion stabilizers used in each example are shown in Table 2 below.

[0084] [Table 2]

[0085]

[0086] <Evaluation of Powder Samples>

[0087] A. Particle size distribution

[0088] The powder sample was dispersed in toluene, added into the device with a flow rate of 55%, treated with 40W ultrasound for 5 times, each for 120 seconds, and then the particle size distribution was measured using Microtrac S3500.

[0089] The particle size distribution span is calculated by the following formula.

[0090] Particle size distribution span = (D 90 -D 10 ) / D 50

[0091] B. EIS

[0092] 100 mg of powder sample was placed in a mold with a diameter of 10 mm, pressed at a pressure of 310 MPa, and indium (In) electrodes were set respectively to prepare the battery cell. Impedance was measured using a constant potential meter (Potentiostat) / constant current meter (Galvanostat) (VSP-300). At this time, the frequency range was 0.1 Hz to 1 MHz, and the amplitude voltage was 100 mV.

[0093] The resistance value was obtained from the arc of the Nyquist plot of the impedance measurement result, and the ionic conductivity was calculated taking into account the area and thickness of the sample.

[0094] C. Ratio of ionic conductivity to particle volume (R)

[0095] The particle size distribution is measured in μm. 50 The value is taken as the representative value of the powder sample, and the volume of the spherical particle is calculated by assuming that the spherical particle has this value as the diameter. Next, the ionic conductivity value of the powder sample measured in mS / cm is divided by the ionic conductivity value in μm. 3 The ratio R (unitless) is defined by the volume of the spherical particle.

[0096] D. Conductivity

[0097] 100 mg of the powder sample was placed in a mold with a diameter of 10 mm, pressed at a pressure of 310 MPa, and stainless steel (SUS) electrodes were set to prepare a battery cell. A voltage of 1 V was applied using a constant potential meter / constant current meter (VSP-300), and the current was measured after 1 hour. The conductivity was calculated by considering the area and thickness of the sample relative to the measured current.

[0098] E. XRD

[0099] The XRD spectrum was measured using a Malvern panalytical Aeris instrument (Cu kα, λ=1.5406Å) at a voltage of 40 kV and a current of 15 mA.

[0100] Figure 1 and Figure 2 This is a graph that organizes the size of pulverized particles and the recovery rate of powder according to the amount of balls used as a dispersion medium.

[0101] Reference Figure 1 When a dispersion stabilizer is used, it is known that the particle size decreases according to the amount of balls added, so it is easy to adjust the particle size. However, when a dispersion stabilizer is not used, it is known that the particle size does not decrease above a certain level even if the amount of balls increases, so it is difficult to adjust the particle size.

[0102] Reference Figure 2 When a dispersion stabilizer is used, it is found that even if the amount of balls added increases, a high recovery rate is maintained, but when a dispersion stabilizer is not used, the amount of powder firmly attached to the balls and reaggregated increases, so the recovery rate decreases sharply.

[0103] The particle sizes and recovery rates of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 3 below.

[0104] [Table 3]

[0105]

[0106] Figure 3 This is a graph summarizing the particle size analysis results of the powder samples of Examples 5 to 11 and Comparative Example 5. Figure 3 In the case of Examples 5 to 11 using methyl isobutyl ketone as a dispersion stabilizer, it can be seen that the average particle size (D50) is significantly reduced compared to Comparative Example 5 which does not use a dispersion stabilizer. Table 4 below shows the particle size analysis results of each Example and Comparative Example.

[0107] [Table 4]

[0108]

[0109] Figure 4 Graph showing the results of recovery rate measurement. Figure 4 In the case of the example, it can be seen that a higher recovery rate is shown compared with Comparative Example 5. The following Table 5 is a table summarizing the measurement results of the recovery rate according to the content of the dispersion stabilizer.

[0110] [Table 5]

[0111]

[0112] Figure 5 Graph showing the measurement results of ion conductivity. Figure 5 , the ionic conductivity values ​​of the embodiments are lower than those of the comparative examples as a whole. According to the judgment, this is because, in the case of the comparative examples, since no dispersion stabilizer is used, the size of the particles cannot be adjusted to the desired level, so that the powder sample of the comparative example has a smaller particle size than the powder sample of the embodiment, so that the interface between the particles increases during molding. Therefore, it can be seen that for the same level of particle size, in order to compare the embodiments and the comparative examples, a standardized benchmark is required, and a benchmark called the ratio (R) of ionic conductivity to particle volume is introduced in the present invention. Figure 6 It is a graph showing the ratio of ion conductivity to particle volume in Examples and Comparative Examples.

[0113] Reference Figure 6, the ratio of the ionic conductivity of the embodiment to the particle volume is higher than the ratio of the ionic conductivity of the comparative example. Therefore, it can be expected that the ionic conductivity of the powder sample of the embodiment is higher than the ionic conductivity of the powder sample of the comparative example assuming the same size.

[0114] Figure 7 It is a graph showing the XRD analysis results of the powder sample before particle size control synthesized in the experimental example and the powder sample of Example 7 after wet pulverization.

[0115] Reference Figure 7 It can be seen that compared with the Li6PS5Cl benchmark value (reference) peak, a crystalline phase of Li6PS5Cl was synthesized, and the Li6PS5Cl phase was maintained even after pulverization.

[0116] Figure 8 This is a graph summarizing the particle size analysis results of the powder samples of Examples 12 to 18. For comparison, the particle size data of Example 7 and Comparative Example 5 are also shown.

[0117] Reference Figure 8 In the case of Examples 12 to 18 using a ketone dispersion stabilizer, it can be seen that the average particle size (D50) is significantly reduced compared to Comparative Example 5 in which no dispersion stabilizer is used.

[0118] Table 6 below shows the particle size analysis results of each Example and Comparative Example.

[0119] [Table 6]

[0120]

[0121] Fig. 9 : is a graph that summarizes the measurement results of the recovery rates of the powder samples of Examples 12 to 18. For comparison, the recovery rates of Example 7 and Comparative Example 5 are also shown. Fig. 9 In the case of the example, it can be seen that a higher recovery rate is shown compared with Comparative Example 5. Table 7 below is a table summarizing the measurement results of the recovery rate according to the type of dispersion stabilizer.

[0122] [Table 7]

[0123]

[0124] Fig.10 and Fig.11 : is a graph showing the measurement results of the ionic conductivity and the ratio of the ionic conductivity to the particle volume of the powder samples of Examples 12 to 18. For comparison, Example 7 and Comparative Example 5 are also shown. Fig.11It can be seen that the ratio of the ion conductivity to the particle volume of the embodiment is higher than the ratio of the ion conductivity to the particle volume of the comparative example. Fig.12 It is a graph showing the measurement results of the electrical conductivity of Examples and Comparative Examples.

[0125] Reference Fig.12 , it is judged that there is no significant difference in the conductivity between the embodiment and the comparative example. Therefore, the conductivity does not change with the content and type of the dispersion stabilizer, which means that there is almost no residual dispersion stabilizer.

[0126] The preferred embodiments of the present invention are described in detail above, but those skilled in the art will appreciate that various modifications may be made to the above embodiments without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be determined by the scope of the claims and the equivalents of the scope of the claims.

[0127] Industrial Applicability

[0128] The present invention can be applied to solid electrolytes of lithium secondary batteries.

Claims

1. A method for preparing a sulfide-based solid electrolyte, comprising the following steps: preparing a sulfide-based solid electrolyte material as a compound containing Li, A, and S, A containing at least one of P, Si, Ge, Al, B, and Sn; and a micronization step of wet-crushing the sulfide-based solid electrolyte material; Here, an organic solvent is used as a dispersion medium used in the wet pulverization, and a ketone solvent is used as a dispersion stabilizer.

2. The method for preparing a sulfide-based solid electrolyte according to claim 1, characterized in that: The content of the dispersion stabilizer is 0.01-10 parts by volume relative to 100 parts by volume of the dispersion medium.

3. The method for preparing a sulfide-based solid electrolyte according to claim 2, characterized in that: The content of the dispersion stabilizer is 0.1-2 parts by volume relative to 100 parts by volume of the dispersion medium.

4. The method for preparing a sulfide-based solid electrolyte according to claim 1, characterized in that: The two hydrocarbon groups or hydrocarbon derivatives in the ketone solvent are connected to a carbonyl group (C=O), and at least one of the two hydrocarbon groups or hydrocarbon derivatives has 5 or less carbon atoms.

5. The method for preparing a sulfide-based solid electrolyte according to claim 4, characterized in that: The ketone solvent includes at least one of methyl isobutyl ketone, acetone, butyl methyl ketone, diethyl ketone, diisobutyl ketone, methyl ethyl ketone, methyl amyl ketone and methyl propyl ketone.

6. The method for preparing a sulfide-based solid electrolyte according to claim 1, characterized in that: The organic solvent includes at least one of a hydrocarbon-based non-polar solvent and an aromatic compound.

7. The method for preparing a sulfide-based solid electrolyte according to claim 1, characterized in that: After the micronization step, the method includes removing the dispersion medium and the dispersion stabilizer to recover the powder, wherein the weight of the recovered powder is more than 80% of the weight of the added powder.